2008
DOI: 10.1016/j.ydbio.2008.02.059
|View full text |Cite
|
Sign up to set email alerts
|

Large P body-like RNPs form in C. elegans oocytes in response to arrested ovulation, heat shock, osmotic stress, and anoxia and are regulated by the major sperm protein pathway

Abstract: As Caenorhabditis elegans hermaphrodites age, sperm become depleted, ovulation arrests, and oocytes accumulate in the gonad arm. Large ribonucleoprotein (RNP) foci form in these arrested oocytes that contain RNA-binding proteins and translationally masked maternal mRNAs. Within 65 min of mating, the RNP foci dissociate and fertilization proceeds. The majority of arrested oocytes with foci result in viable embryos upon fertilization, suggesting that foci are not deleterious to oocyte function. We have determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
214
5
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(253 citation statements)
references
References 67 publications
20
214
5
4
Order By: Relevance
“…The different locations and morphologies of cytoplasmic RNA accumulations and enlarged P granules in csr-1(RNAi) suggest that P granules are not the sites of excessive RNA accumulation. Previous studies have shown that depletion of sperm and arrested ovulation cause RNA to accumulate in the rachis; this phenotype is regulated by the major sperm protein pathway (Schisa et al 2001;Jud et al 2008). csr-1(RNAi) animals exhibited no obvious defects in fertilization or ovulation, suggesting that RNA accumulation in csr-1(RNAi) animals is not caused by loss of the major sperm protein pathway.…”
Section: Resultsmentioning
confidence: 95%
“…The different locations and morphologies of cytoplasmic RNA accumulations and enlarged P granules in csr-1(RNAi) suggest that P granules are not the sites of excessive RNA accumulation. Previous studies have shown that depletion of sperm and arrested ovulation cause RNA to accumulate in the rachis; this phenotype is regulated by the major sperm protein pathway (Schisa et al 2001;Jud et al 2008). csr-1(RNAi) animals exhibited no obvious defects in fertilization or ovulation, suggesting that RNA accumulation in csr-1(RNAi) animals is not caused by loss of the major sperm protein pathway.…”
Section: Resultsmentioning
confidence: 95%
“…For example, in response to heat stress, key eIFs are phosphorylated, which correlates with a general reduction in the abundance of translating ribosomes (Nousch and Eckmann, unpublished data). A different and more indirect indication is the presence of large cytoplasmic RNP structures in response to environmental stresses (Jud et al 2008 ) . The protein composition of these structures resemble in their protein components and dynamics stress granules of yeast or mammalian cells, which are thought to contain repressed translation initiation complexes (Buchan et al 2011 ;Kedersha et al 2005 ) .…”
Section: Events In the Cytoplasm: Mrna Quantity Versus Translatabilitymentioning
confidence: 99%
“…After the four-cell stage, MEX-3 begins to disappear from the embryo. A small amount of MEX-3 remains in the posterior germline lineage, where it localizes to RNA-rich bodies including germ granules in early embryos and CAR-1/CGH-1 granules in late oocytes (3,(5)(6)(7).…”
mentioning
confidence: 99%